TEACHING SIMPLE PAST TENSE USING VIDEO CLIPS WITH ENGLISH SUBTITLES AT X MIPA GRADE OF SMAN 1 TEMBILAHAN - Imbana Saputra; Samsul Amri; Syafrizal (J-Shelves of Indragiri (JSI), 2022)
This study aims to improve students' ability to understand the Simple Past Tense. This research is a Classroom Action Research (CAR). This research was carried out in one cycle in one cycle there were four meetings and in this study included the stages of planning, observation, and reflection. research participants are students of class X MIPA 3 in the academic year 2021/2022. The number of participants is half of the students in the class due to the current condition of the corona virus outbreak so that only 16 students were used as students in this research class, there were 7 boys and 6 girls. In this study, learning is not only explained through the material but students are given several video clips as a treatment which contains simple past tense sentences so that learning is more fun and not boring besides that students can also understand the simple past tense material easily so that students' understanding of the simple past tense is increasing. The results showed that using video clips with English subtitles could improve students' understanding of the simple past tense. This can be proven from the results of the students' average scores. The average score of students before the action was 44 with a sufficient category. Then at the second meeting, 74 in the good category then increased again at the third meeting, namely 87 in the very good category and at the last meeting it decreased slightly, namely 84 but still in the very good range. The students really liked the learning process using video clips. Based on the previous statement, it can be concluded that teaching Simple Past tense using video clips with English subtitles can improve students' understanding of the simple past tense in class X MIPA SMAN 1 Tembilahan.